Shapley Supercluster Survey: construction of the photometric catalogues and i-band data release. Issue 4 (9th September 2015) - Mercurio, A.; Merluzzi, P.; Busarello, G.; Grado, A.; Limatola, L.; Haines, C. P.; Brescia, M.; Cavuoti, S.; Dopita, M.; Dall'Ora, M.; Capaccioli, M.; Napolitano, N.; et al.
Abstract: The Shapley Supercluster Survey is a multi-wavelength survey covering an area of ∼23 deg 2 (∼260 Mpc 2 at z  = 0.048) around the supercluster core, including nine Abell and two poor clusters, having redshifts in the range 0.045–0.050. The survey aims to investigate the role of the cluster-scale mass assembly on the evolution of galaxies, mapping the effects of the environment from the cores of the clusters to their outskirts and along the filaments. The optical ( ugri ) imaging acquired with OmegaCAM on the VLT Survey Telescope is essential to achieve the project goals providing accurate multi-band photometry for the galaxy population down to m * + 6. We describe the methodology adopted to construct the optical catalogues and to separate extended and point-like sources. The catalogues reach average 5σ limiting magnitudes within a 3 arcsec diameter aperture of ugri  = [24.4, 24.6, 24.1, 23.3] and are 93 per cent complete down to ugri  = [23.8, 23.8, 23.5, 22.0] mag, corresponding to ∼ m * r + 8.5. The data are highly uniform in terms of observing conditions and all acquired with seeing less than 1.1 arcsec full width at half-maximum. The median seeing in r band is 0.6 arcsec, corresponding to 0.56 kpc $h^{-1}_{70}$ at z  = 0.048. While the observations in the u, g and r bands are still ongoing, the i -band observations have been completed, and we present the i -band catalogue over the whole survey area. The latter is released and it will be regularly updated, through the use of the Virtual Observatory tools. This includes 734 319 sources down to i  = 22.0 mag and it is the first optical homogeneous catalogue at such a depth, covering the central region of the Shapley supercluster.